Inferences in the First Person - Gianfranco Soldati (Rosenberg & Sellier, 2017)
This paper deals with the experiential basis of deductive reasoning. It concentrates on the case of inferential knowledge in the first person. It first describes the specific kind of entitlement involved in such knowledge. A comparison is then made with inferential knowledge involving other indexical and demonstrative concepts. The entitlement involved in those cases is based on the fact that indexicals such as “here” and “now” are associated with experiential concepts. It is submitted that the concept associated to the expression “I” is an experiential concept application of which presupposes a special sensitivity to the identity of the self through time.